Psychological impacts of maternal migration on left-behind children: a cross-cultural review - Al-Azzeh, Dana; Diab, Jasmin Lilian (Frontiers in Psychology, 2025)
In the pursuit of a brighter future for their children, many female migrant workers leave their home countries to seek employment abroad, often as caregivers for families in wealthier nations. This decision necessitates prolonged separation from their own children, depriving them of the opportunity to witness and participate in crucial stages of their children’s development. The absence of these mothers, combined with inconsistent caregiving in their stead, significantly increases the vulnerability of left-behind children to mental health challenges, such as depression, anxiety, and difficulties in forming emotional bonds with others. Moreover, even after the migrant mother’s eventual return, the disruptions in attachment often result in long-term consequences, including strained and distant relationships with their children. This article explores the complex impact of maternal migration on the mental well-being of left-behind children across various cultural contexts. It highlights key findings, such as the role of communal caregiving practices in mitigating adverse effects in some societies, while noting that these practices are not a complete solution. The study underscores the need for culturally sensitive mental health interventions and policy measures to support the well-being of children affected by maternal migration globally.